Decision Making, Artificial Intelligence, and ESG Regulations - Adamus-Matuszyńska, Anna (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
The growing incorporation of Artificial Intelligence (AI) into environmental, social, and governance (ESG) practices, alongside non-financial reporting, is reshaping decision-making processes within organizations. This research investigates the multifaceted impact of AI on ESG decision making, exploring how AI-driven tools and analytics support strategic decisions pertaining to the implementation of the CSRD Directive. The research method is the analysis of the content of documents and their examination in terms of determining the basic areas of decision-making, identifying the risks associated with these decisions, and developing a methodology for using AI in these decision-making processes. The analysis concludes that although AI can provide substantial support in executing the CSRD directive, it is incapable of substituting a knowledgeable team familiar with the company’s specific environment. The research did not include any empirical methods that would allow one to understand the practical possibilities of using AI in decision-making processes related to the implementation of the CSRD directive by companies. The study exposes the significant scope for exploration in the practical applications of AI, serving as a potential foundation for advancing decision-making processes within contemporary corporate management.